Unital Four-Dimensional Lattice-Ordered Algebras with a Distributive Basis. (29th June 2011) - Akkurt, Mustafa; Alshair, Zainab; Lamar, Lena; Ma, Jingjing
Abstract : All unital four-dimensional lattice-ordered algebras with ad -basis are constructed.